Closed-Loop Supply Chain Adoption and The Mediating Effect of Green Capabilities - Evidence from Malaysia - Fadilah, Siali; Thurasamy, Ramayah (Assumption University, Thailand, 2023)
The concept of a closed-loop supply chain (CLSC) is concerned with the recovery of value from returned consumer products via resales. The rapidness of economic growth gives manufacturers no option but to shorten the product life cycle. Consequently, new versions following product upgrades happen too fast, increasing product returns in the form of End-of-Life (EOL) or End-of-Use returns. This issue has become crucial with a lack of processes for effectively handling product returns in Malaysia; thus, firms often use a third party, although this is considered improper by global standards. Therefore, this research aims to clarify the connection between Institutional Theory and the Natural Resource-Based View (NRBV) Theory in light of CLSC adoption in Malaysia. The findings highlight the role of government in overpowering competitors and customers in adopting a CLSC. The study’s limitations include presenting a formation of ideas that haven’t been previously linked in a research framework, setting the stage for more research in this area.